Bacteriophage and bacteriophage-like structures carried by Bacillus medusa and their effect on sporulation. - Hendry, G S (1976)
Bacillus medusa was found to carry three phages or phagelike structures named phi med-1, phi med-2, and phi med-3. phi med-1 is a minute, 25-nm-diameter particle without a tail. It was extracted from the sporulation lysate of a phi med-2-minus strain of B. medusa and purified by differential centrifugation. The nucleic acid from this structure was shown to be orcinol positive, alkali sensitive, RNase sensitive, and DNase resistant. An RNase-resistant core of nucleic acid was not found, indicating that it was single-stranded RNA. A host strain has not yet been found for phi med-1. Phage phi med-3 was induced with mitomycin C or UV light and consisted of empty heads of 57 nm in diameter, whereas phi med-2 induced with mitomycin was a phage of 60-nm head diameter and 220-nm tail length. The sporulation sequence proceeded faster in those mutants lacking phi med-2, and when the phage was reintroduced to B. medusa the extended wild-type sporulation sequence was observed. B. thuringiensis var. schwetzova was sensitive to phi med-2 and yielded small turbid plaques. B. medusa produced small numbers of phi med-2 during growth. The other phage may be produced at the same time but were not detected. Phi med-1 was found in sporulating cells by electron microscopy techniques. Its release from these was demonstrated by both electron microscopy techniques and a radioactive assay. It appears to participate in the formation of a surface layer on the parasporal inclusion of B. medusa.